1993
DOI: 10.1002/eqe.4290220306
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic response and design criteria of plan‐wise asymmetric systems

Abstract: SUMMARYThe study of the torsional response of buildings in the inelastic range of behaviour is of great interest since the ability of structures to resist strong earthquakes mainly relies on their ductility and capacity for energy dissipation. Furthermore, an examination of the performance of structures during past earthquakes demonstrates that plan-asymmetric buildings suffered greater damage due to torsional response. The paper deals with this subject by analysing a model which idealizes a one-storey buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Because of such an evidence, large research efforts have been devoted to examining effects of the lateral-torsional coupling on building seismic behaviour (Goel and Chopra, 1990;De Stefano et al, 1993, 1998De Stefano and Rutenberg, 1999) and to developing and proposing design procedures (Goel and Chopra, 1990;Chandler and Duan, 1992;Duan and Chandler, 1992;Tso and Zhu, 1992;Zhu and Tso, 1992; aimed at providing both plan-regular and plan-irregular systems with a similar level of seismic protection. To this purpose, most studies on seismic response of asymmetric structures have analysed response of single-storey models (Goel and Chopra, 1990;Tso and Zhu, 1992;Zhu and Tso, 1992;De Stefano et al, 1993, 1998De Stefano and Rutenberg, 1999; representing the most extreme idealisation of plan irregular buildings. Such models usually consist of a floor deck, rigid in its own plane and supported by massless, axially inextensible vertical resisting elements, characterised by a bi-linear elastic-hardening behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Because of such an evidence, large research efforts have been devoted to examining effects of the lateral-torsional coupling on building seismic behaviour (Goel and Chopra, 1990;De Stefano et al, 1993, 1998De Stefano and Rutenberg, 1999) and to developing and proposing design procedures (Goel and Chopra, 1990;Chandler and Duan, 1992;Duan and Chandler, 1992;Tso and Zhu, 1992;Zhu and Tso, 1992; aimed at providing both plan-regular and plan-irregular systems with a similar level of seismic protection. To this purpose, most studies on seismic response of asymmetric structures have analysed response of single-storey models (Goel and Chopra, 1990;Tso and Zhu, 1992;Zhu and Tso, 1992;De Stefano et al, 1993, 1998De Stefano and Rutenberg, 1999; representing the most extreme idealisation of plan irregular buildings. Such models usually consist of a floor deck, rigid in its own plane and supported by massless, axially inextensible vertical resisting elements, characterised by a bi-linear elastic-hardening behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a specific design method defined for two types of eccentric systems without strength eccentricity and with a strength eccentricity equal to stiffness eccentricity, Tso and Ying (1990) highlighted that the flexible edge is more sensitive to the torsional effects and could experience additional ductility demands when the strength eccentricity exists. These conclusions have also been emphasised by other researchers (De Stefano et al, 1993;Chopra, 1990, 1991). However, Sadek and Tso (1989) observed that an increase in the strength eccentricity may lead to an increase in the torsional response of asymmetric structures.…”
Section: Introductionmentioning
confidence: 51%
“…Model 6 is a model with uniform strength distribution and stiffness eccentricity. Models 7 and 8 are known as "optimum configuration" models according to the study of De Stefano et al [32]. In model 7, the distance between the mass center and strength center is 0.25 of the distance between the mass center and the stiffness center, while in model 8, the strength center is between the mass and stiffness centers and in an equal distance from each of them.…”
Section: Studied Modelsmentioning
confidence: 99%